Kemampuan Literasi Digital Guru Sekolah Dasar terhadap Aplikasi Canva - Rahma Ramadhani Shabahal Fauziah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In today's rapidly growing technological era, teachers need to develop digital skills, especially in the creation of learning media, because their creativity is needed. Understanding digital literacy in education teachers can more easily fulfill the needs of their tasks in the process of teaching students. In addition, the students involved in learning using digital literacy will develop skills that are in line with the times. The seriousness and desire of SDN Bantargebang 02 teachers is very high, especially in learning digital literacy and utilizing media such as the Canva application which can help make the learning process more interesting. However, to improve the quality of teachers, the availability of facilities that support the needs such as special training or workshops to learn this digital application is needed. The current curriculum paradigm needs adaptation which takes time. Senior teachers who must adapt to the changing times in education era 4.0 require government attention to improve the quality of teachers through facilities and field support.